Faktor Yang Mempengaruhi Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) - Nurdin, St Surya Indah; Manjurungi, Gia Arista Putri; Umar, Siskawati; Ishak, Fifi; Mulyaningsih, Sri; Rauf, Efri Leny; Hiola, Fidyawati Aprianti A.; Ahmad, Zul Fikar (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
The use of contraceptives can reduce 32% of maternal mortality rates and 10% of child mortality rates in the world. This study aims to determine the influence of factors that influence the use of MKJP in the work area of the Suwawa Tengah Health Care. This study uses an analytical observational method with a cross-sectional approach. The sample used was a total sampling method of 28 respondents. Data collection using a questionnaire sheet and data analysis using chi-square test analysis with a significance level of 95% (α = 0.05). The age factor obtained a p value = 0.029 and statistical tests through a 95% IK value of 10.7. The parity factor obtained a p value = 0.046, OR = 7.125. The education factor obtained a p value = 0.046 OR = 8.000. The work factor obtained a p value = 0.078, OR = 8. The knowledge factor obtained a p value = 0.008, OR = 15.00. Husband support factor obtained p value = 0.023, OR = 8.000 and health worker support obtained p value = 0.023, OR = 8.00. The conclusion is that there is a relationship between age, parity, education, knowledge, husband support and health worker support with the use of MKJP. There is no relationship between work and the use of MKJP at the Suwawa Tengah Primary Health Care.